Factors Influencing Mobile Banking Adoption - Nur Fariza, Zainol (2011)
Today, the advancement of mobile technologies has provided an opportunity for banking institution in introducing new financial innovations. One of the emerging financial innovations introduced by banking institution is mobile banking. This study adopts a technology acceptance model (TAM) to investigate factors that determine an individual’s intention to use mobile banking by bank customers among UUM staff. The additional of TAM includes credibility, self-efficacy, compatibility and normative pressure. A results support construct of TAM and construct of other theories in predicting bank customers’ behavioural intention to use mobile banking. Understanding what influences users to accept mobile banking can be beneficial to banks, system developers and marketing practitioners in developing and marketing mobile banking services that will be acceptable by the target market.